Respon Pemberian KNO3 dan Pupuk Agrodyke Terhadap Hasil Tanaman Jeruk Siam (Citrus nobillis var microcarva L.) - Wayan Hendrajaya; Ni Komang Alit Astiari; Ni Putu Anom Sulistiawati (Fakultas Pertanian, Universitas Warmadewa, 2019)
This study aims to determine the response of KNO3 and Agrodyke fertilizer to the yield of siam oranges and their interactions. This research is a field experiment conducted in Banjar Belancan, Belancan Village, Kintamani Subdistrict, Bangli Regency starting from January to July 2018. This study uses a Randomized Block Design (RBD) with 2 factors arranged factorially. the first factor was tried was KNO3 which consisted of 3 levels namely K0 (0 g/plant), K1 (20 g/plant) and K2 (40 g/plant, while the second factor that was tried was Agrodyke (A) fertilizer consisting of 4 levels namely A0 (0 g/plant), A1 (15 g/plant), A2 (30 g/plant) and A3 (45 g/plant), thus there are 12 combination treatments, each repeated 3 times so that 36 trees are needed Siamese plants interaction between KNO3 treatment with Agrodyke fertilizer treatment (KxA) had no significant effect (Pâ‰¥0.05) on all observed variables KNO3 treatment The highest fruit weight per tree was obtained in KNO3 treatment with a dose of 40 g / plant (K2) ie 12.70 kg increased by 50.29% when compared to the lowest yield in the treatment without KNO3, which was only 8.45 kg, the highest yield of fruit per tree was obtained in Agrodyke treatment with a dose of 30 g/plant (A2), namely 12.90 kg has increased 61.47% when compared to h the lowest acyl in treatment without Agrodyke is 7.89 kg.